Pengaruh Promosi Online Dan Persepsi Harga Terhadap Keputusan Pembelian Pada Aplikasi Gofood Bakso Jaya Di Bekasi Utara - Akbar, Mulky; Maulina, Anita; Arizona, Anisa (JAMBIS : Jurnal Administrasi Bisnis, 2024)
There are many growing marketing methods. Gojek represents a service provider company in the form of online-based transportation, food delivery, delivery of goods and others. Bakso Jaya as a meatball restaurant provides online delivery service on the GoFood application. The objective of this study was to find out the effect of online promotion and perceived price on purchasing decision on the GoFood Bakso application in North Bekasi. The research method used descriptive quantitative and associative methods. The data were collected using a questionnaire based on a Likert scale. The population in this study are Bakso Jaya customers who have bought using the GoFood application. The sample of this research was drawn using non-proballity sampling method with accidental sampling technique. The samples obtained were 145 samples. The data were analyzed using multiple linier regression analysis with SPSS Version 26 software. The result of this study indicated that online promotion (X1) influenced significantly and positively the purchasing decisions (Y) of 0.445 or 44.5%. The perceived price (X2) influenced significantly and positively the purchasing decisions (Y) of 0.532 or 53.2%. The online promostions (X1) and perceived price (X2) influenced significantly and positively the purchasing decisions (Y) of 0.616 or 61.6%